2017
DOI: 10.3389/fcvm.2017.00064
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Antioxidants in the Preservation of Vascular Function and the Modulation of Health and Disease

Abstract: In vascular diseases, including hypertension and atherosclerosis, vascular endothelial dysfunction (VED) occurs secondary to altered function of endothelial nitric oxide synthase (eNOS). A novel redox regulated pathway was identified through which eNOS is uncoupled due to S-glutathionylation of critical cysteine residues, resulting in superoxide free radical formation instead of the vasodilator molecule, nitric oxide. In addition, the redox sensitive cofactor tetrahydrobiopterin, BH4, is also essential for eNO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 151 publications
1
40
0
2
Order By: Relevance
“…Several in vitro and epidemiological studies suggested an important role of herbal medicine extracts rich in polyphenols to preserve vascular health and to prevent cardiovascular diseases [13]. The oxidative stress results from a cellular imbalance between the effect of pro and antioxidants, in favor of the first, being considered as a factor that contributes to the atherogenic process [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and epidemiological studies suggested an important role of herbal medicine extracts rich in polyphenols to preserve vascular health and to prevent cardiovascular diseases [13]. The oxidative stress results from a cellular imbalance between the effect of pro and antioxidants, in favor of the first, being considered as a factor that contributes to the atherogenic process [14].…”
Section: Discussionmentioning
confidence: 99%
“…Fibulin-3 has previously been suggested as an arterial growth factor [3, 6] as injection of Fibulin-3 protein increases aortic wall thickness in spontaneously hypertensive rats [10]. However, Fibulin-3 reduces systolic blood pressure and improves vascular health [10], at least in part, by reducing aortic oxidative stress [10-12] and expression of matrix gelatinases [10, 13]. In vascular smooth muscle cells (VSMCs), gelatinase expression and activity are stimulated by excessive oxidative stress [14-17].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has been shown to greatly improve cardiovascular function, in part through the improved bioavailability of nitric oxide, enhanced endogenous antioxidant defense and a lowering of the expression of ROS-forming enzymes. 21,22 We suppose that physical activity modulates endothelial response to lipids and a synergy with a healthy diet such as a Mediterranean diet improves this positive effect. Endothelial dysfunction, which is a central mechanism leading to CVD and the redox switch could be modulated by physical activity (that acts directly on endothelium) and dietary factors reducing the risk of CVD onset.…”
Section: Discussionmentioning
confidence: 99%